Curiosity and networks of possibility. Issue 1 (June 2023) - Zurn, Perry; Bassett, Dani S.
The concept of possibility has long been intertwined with the discourse of curiosity. The way things might be can disturb the way things are, but we have to be ready for it. Curiosity provides that readiness. There is a kind of critical curiosity that opens the space of possibility by exploiting the instability of the present, second guessing its current contours and exploring how else the world might be constructed or understood. Put differently, it is because of curiosity that revolutions in science, knowledge, and society become possible. The two work in tandem. If curiosity can be a critical comportment toward the possible, then to fully understand possibility one must also understand curiosity. In this brief essay, we take a moment to think that jointure. How might curiosity studies illuminate possibility studies? From our respective vantage points of philosophy and neuroscience, we analyze possibility through curiosity. In doing so, we ultimately illuminate the novelty bias that informs both concepts, the network structures that characterize them, and the adjacent worlds and opportunities they offer.